Sources of resistance to cassava anthracnose disease - Owolade, O.; Dixon, A.; Adeoti, A.; Osunlaja, S. (Academic Journals, 2005)
A total of 436 African landraces and 497 improved cassava genotypes were planted in 1996, 1997, 1998 and 1999 growing seasons.. These were evaluated for their reactions to cassava anthracnose disease (CAD) under natural infection conditions at Ibadan (a high infection zone). The severity of the disease was determined by counting the total number of canker/plants and measuring the diameter the cankers. Data were collected at 6, 9 and 12 months after planting. The four-year data were pooled and subjected to statistical analysis. Result showed that of the 436 improved germplasm evaluated, 10 were resistant, 64 moderately resistant, 328 were moderately susceptible, and 95 were highly susceptible. The results also showed that 45 of the landraces were resistant, 87 moderately resistant, 354 were moderately susceptible, whereas 60 were highly susceptible. Of the resistant landraces and the improved, TME 19, TME 53, TME113, TME 244, TME 475, and TME 523; I85/02015 and I8700028 were completely free of cankers. The resistant genotypes have been introgressed into broad-based breeding populations to diversify resistance to CAD in newly improved genotypes.